Phenotypic diversity and characterization of several avocado (Persea americana) germplasm grown in Subang, West Java, Indonesia - DIAN RAHMAH FITRI; SLAMET SUSANTO; LIFERDI LUKMAN; DENY SUKMANA (Society for Indonesian Biodiversity, 2026)
Abstract. Fitri DR, Susanto S, Lukman L, Sukmana D. 2026. Phenotypic diversity and characterization of several avocado (Persea americana) germplasm grown in Subang, West Java, Indonesia. Biodiversitas 27 (4): d270430. https://doi.org/10.13057/biodiv/d270430. Avocado (Persea americana) exhibits broad morphological and phenological variation that supports germplasm characterization and the evaluation of phenotypic diversity for cultivar development. This study compared the morphological, phenological, yield, and fruit-quality characteristics of three Lampung avocado accessions (Lampung 1, Lampung 2, and Lampung 3) with the commercial cultivar Miki (Cipedak) under relatively uniform environmental conditions in Subang, West Java. Observations included vegetative growth, flowering and harvesting periods, leaf morphology, reproductive traits, fruit physical characteristics, productivity, edible portion, and biochemical traits (fat and sugar contents). Data were analyzed using analysis of variance followed by Tukey’s HSD test to determine significant differences among accessions. The results showed significant variations among accessions, particularly in leaf size and area, fruit set, fruit size and weight, edible portion, fat and sugar contents. The fruit of Lampung 1 was 56% heavier than Miki, Lampung 2 showed comparable fruit weight, and Lampung 3 produced smaller fruits. Lampung 1 and Lampung 2 exhibited a 14% higher edible portion compared to Miki. Differences were also observed in fruit productivity, with Lampung 1 producing the highest yield at 7.13 kg per plant, while Lampung 3 had the lowest. Variations in sugar and fat contents were observed among accessions. Lampung 2 showed higher fat content, Lampung 1 had comparable fat content to Miki, while Lampung 3 exhibited higher fat and sugar contents. The relatively higher fat content observed in certain accessions indicates their potential for further evaluation for value-added utilization. Overall, Lampung 1 and Lampung 2 demonstrate better yield and fruit quality traits. However, as this study was conducted at a single location and during one growing season, multi-location and multi-season evaluations are required to confirm yield stability, adaptability, and further potential utilization.